PW 0318 Child pedestrian risk and social equity: spatial distribution of roadway safety features in toronto, canada. (November 2018) - Rothman, Linda; Cloutier, Marie-Soleil; Manaugh, Kevin; Howard, Andrew; Macpherson, Alison; Macarthur, Colin
Abstract : Investments in road design features are made to improve pedestrian safety in urban areas. Pedestrian motor vehicle collisions (PMVC); however, remain common, and occur at higher frequency in lower income neighborhoods. The objective of this study was to compare child PMVC rates and the distribution of roadway environment features related to child pedestrian safety in low versus high income clusters, in Toronto, Canada. Spatial cluster detection by census tract identified low and high income clusters using Canadian census data. Police-reported data of 2185 PMVCs involving children ages 5–14 from 2001–2010 were mapped with speed humps, crossing guards, missing sidewalks, one-way streets and local roads. Relationships between roadway features and low versus high income clusters were examined using multiple logistic regression. Of 524 census tracts, fifty eight (11%) were in high and 44 (8%) were in low income clusters. Collision rates were almost 6 times higher in low income clusters. For every km/10 km road increase of speed humps there was a 65% lower odds, for every km/10 km road increase in local roads there was a 38% lower odds and for every additional crossing guard/10 km road there was a 43% greater odds of being in a lower income cluster. Fewer lower speed local roads and speed humps in lower income areas may put children at increased risk. The inequity in spatial distribution of speed humps may due to process of request which is initiated by the community and may favour higher income communities. More school crossing guards may reflect more children walking in lower income areas, as well as attempts to ameliorate more dangerous road environments with higher PMVC rates. Policy implications relate to the equitable distribution of roadway features to provide safe pedestrian environments.